Effective interventions to address maternal and child malnutrition: an update of the evidence. (May 2021) - Keats, Emily C; Das, Jai K; Salam, Rehana A; Lassi, Zohra S; Imdad, Aamer; Black, Robert E; Bhutta, Zulfiqar A
Summary: Malnutrition—consisting of undernutrition, overweight and obesity, and micronutrient deficiencies—continues to afflict millions of women and children, particularly in low-income and middle-income countries (LMICs). Since the 2013 Lancet Series on maternal and child nutrition, evidence on the ten recommended interventions has increased, along with evidence of newer interventions. Evidence on the effectiveness of antenatal multiple micronutrient supplementation in reducing the risk of stillbirths, low birthweight, and babies born small-for-gestational age has strengthened. Evidence continues to support the provision of supplementary food in food-insecure settings and community-based approaches with the use of locally produced supplementary and therapeutic food to manage children with acute malnutrition. Some emerging interventions, such as preventive small-quantity lipid-based nutrient supplements for children aged 6–23 months, have shown positive effects on child growth. For the prevention and management of childhood obesity, integrated interventions (eg, diet, exercise, and behavioural therapy) are most effective, although there is little evidence from LMICs. Lastly, indirect nutrition strategies, such as malaria prevention, preconception care, water, sanitation, and hygiene promotion, delivered inside and outside the health-care sector also provide important nutritional benefits. Looking forward, greater effort is required to improve intervention coverage, especially for the most vulnerable, and there is a crucial need to address the growing double burden of malnutrition (undernutrition, and overweight and obesity) in LMICs.